Efficacy of Drug Interventions for Chemotherapy-Induced Chronic Peripheral Neurotoxicity: A Network Meta-analysis - Fu, Xiying; Wu, Huijie; Li, Jinyao; Wang, Can; Li, Ming; Ma, Qianqian; Yang, Wei (Frontiers in Neurology, 2017)
Peripheral neurotoxicity is a disturbing issue for cancer patients who are treated with chemotherapy. Several medications have been developed for preventing chemotherapy-induced chronic neurotoxicity (CICNT) however; their relative efficacies have not yet been studied. In this study, we conducted a network meta-analysis to give intervention recommendations. The literature was searched in a variety of databases and eligible studies were chosen based on predefined criteria. Data extraction and statistical analysis was performed and the results are displayed using the odds ratio (OR) and corresponding 95% credible intervals (CrI) with respect to overall and severe neurotoxicity. The medications were ranked according to their surface under cumulative ranking curve (SUCRA) values. The consistency of direct and indirect evidence was also evaluated. We found that patients with amifostine or vitamin E treatment exhibited a lower risk of overall neurotoxicity compared to those using the placebo (amifostine: OR=0.10, 95% CrI: 0.02-0.46; vitamin E: OR=0.08, 95% CrI: 0.01-0.99). In regards to preventing severe neurotoxicity, glutathione and amifostine treatment appeared to be significantly more effective than the placebo (glutathione: OR = 0.19, 95% CrI: 0.04-0.64; amifostine: OR = 0.12, 95% CrI: 0.02-0.48). In summary, amifostine, vitamin E and glutathione treatment is considered to be effective in lowering the risk of CICNT. However, further studies which consider safety are required.